Design of an n-type low glass transition temperature radical polymer. Issue 10 (17th February 2021) - Chi, Teng; Akkiraju, Siddhartha; Liang, Zihao; Tan, Ying; Kim, Ho Joong; Zhao, Xikang; Savoie, Brett M.; Boudouris, Bryan W.
Abstract : We document the design, synthesis, and characterization of the first low glass transition temperature, n-type ( i.e., preferentially-reduced) radical polymer. Abstract : We document the design, synthesis, and characterization of the first low glass transition temperature, n-type ( i.e., preferentially-reduced) radical polymer. Specifically, a macromolecule composed of a polysiloxane backbone that bears galvinoxyl radical pendant groups, poly[2, 6-di- tert -butyl-4-((3, 5-di- tert -butyl-4-(λ 1 -oxidaneyl)phenyl)(4-((3-(methoxydimethylsilyl)propoxy) methyl)phenyl)methylene)cyclohexa-2, 5-dien-1-one] (PGMS), was created as our calculations predicted that the galvinoxyl radical molecular structure would facilitate radical–radical aggregation. In turn, this suggested that charge transport would be rapid in these systems, which would lead to large solid-state electronic conductivity values. After the design and successful synthesis of the PGMS radical polymers, their optical, spin, thermal, and electrochemical properties were evaluated in full. These experiments backed the idea that PGMS has a low glass transition temperature and robust electrochemical behavior. Furthermore, when a PGMS macromolecule was cast into a thin film, a solid-state conductivity of 10 −2 S m −1 was achieved, and this was despite the fact that only ∼36% of the pendant groups contained a galvinoxyl radical. This high conductivity appears to be a direct result of the radical–radical aggregation that occurs due to the molecular design of the galvinoxyl radical species. Therefore, this work highlights the import of developing next-generation open-shell entities for solid-state radical polymer conductors, and it provides a clear path forward for creating high conductivity, non-conjugated conducting macromolecules.